Identifying Traffic Congestion Problems on the Pasar Karombasan Road Segment in Manado City Based on Public Perception: Mengidentifikasi Masalah Kemacetan Lalu Lintas Pada Ruas Jalan Pasar Karombasan Kota Manado Berdasarkan Persepsi Masyarakat - Riko Londah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study addresses the identification of traffic congestion problems on the Karombasan Market road segment in Manado City, involving the community of Karombasan Market users to determine the factors causing congestion in the area. This research employs a qualitative research method by conducting interviews with market users, including buyers, traders, public transport drivers, and others. Data were obtained through observation, interviews, documentation, and analysis of vehicle traffic on the road segment.The analysis results indicate that the flow of vehicles along the Karombasan Market road segment experiences a slowdown, leading to congestion. The community perceives the causes of congestion on this road segment as illegal parking, sidewalk encroachment, vehicles driving against traffic, roadside vending, and the presence of the Karombasan Terminal.This study proposes several solutions to address the causes of congestion on Karombasan Market road segment, which can be utilized by all stakeholders to resolve the issues and ensure smoother traffic flow in the area.